PROCESS AUDITS DEPLOYMENT AS A SUPPORT FOR THE CONTINUOUS IMPROVEMENT: a study in a metallurgical company - Castro, Tales Paschoalino de; Gasparotto, Angelita Moutin Segoria (Revista Interface Tecnológica, 2020)
In the current scenario, where the market is notoriously competitive, companies are increasingly demanded to seek improvements in their processes, aiming to producing with quality, supply what is expected by customers, reduce costs and keep the business profitable. The use of process audits goes toward this propose, since the correct use of this tool allows to verify the effectivess and efficience of the productive processes, and lead them to possible improvements and to the solution of the non conformities found among the process specifications, taks accomplishment, operational procedures, organization, 5S, operational training, among others. This aims to show, through a descriptive research supported by a literature review, the working way of a metallurgical company which started to use process audits as a tool to support the continuous improvement of the foundry process. The main results obtained proved the effectiveness of this tool, collaborating to development of a business culture focus on quality, besides helping to reduce costs and achieve the company’s production goals.
Keywords: Process Audit; Continuous Improvement; Foundry Process